RAZLIKE U NEKIM MOTORIČKIM SPOSOBNOSTIMA KOD UČENIKA OBUHVAĆENIM NASTAVNIM I VANNASTAVNIM AKTIVNOSTIMA IZ KOŠARKE - Miodrag Kocić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The aim of this research was to determine the effects that the third class of physical education during one term had on the mobility of the students tested. 101 students, who were divided into two groups, took part in the research. The first group, which was the control group, was made up of 50 students and the second group was made up of the remaining 51 students who were members of the basketball section. The system for measuring mobility encompassed six different disciplines: the high jump, 20 meters high start race, pull-ups, press-ups, forward bend (and lifting the upper part of the body on the bench). All the results of the research were processed in a usual way giving the information on central and dispersion statistics for all disciplines. The differences between the groups were determined by discriminative analysis